Mental model of the influence of reactant properties on reaction rate - Iqlima Rahayu; Wiji Wiji; Galuh Yuliani; Tuszie Widhiyanti; Sri Mulyani (Pascasarjana Universitas Negeri Medan, 2023)
Reaction rate is still considered difficult by students because it contains abstract concepts and mathematical equations, so students' mental models are not complete. To connect the three levels of representation in the process of addressing chemical problems, learning has to employ mental models as a whole. Therefore, this study aims to obtain students' mental models regarding the influence of reactants properties on reaction rates. This research uses a qualitative descriptive method with the Mental Model Diagnostic Test-Interview About Event (MMDT-IAE) instrument. Based on the research results, there are two types of mental models, namely Partial Understanding (PU) and Partial Understanding with Certain Misconceptions (PU/SM). The effect of surface area on reaction rate, students 1, 2, 3, 4, 6, and 7 answered correctly but could not connect the three levels of representation, while student 5 could not explain the relationship between effective collisions and reaction rate. The influence of structure on reaction rates, students 1, 2, 3, 4, and 7 can answer structure, reactivity and collision theory, while student 5 cannot explain collision theory. Students 1, 4, and 7 can answer all the probing questions but cannot connect the three levels to the influence of ionization energy on the reaction rate. The conclusion of this research is that students' mental models regarding the influence of reactant properties are not complete and there are students who experience misconceptions. The implications of this research are as a basis for teachers to design appropriate learning strategies.Keywords: Mental model; MMDT-IAE; Reaction rate; Three level of representation